Inhibiting CMTM4 reverses the immunosuppressive function of myeloid-derived suppressor cells and augments immunotherapy response in cervical cancer - Bo Yin; Wei Wang; Ang Li; Mengjie Li; Huijuan Zhou; Haoran Hu; Jianyi Ding; Yashi Zhu; Xinxin Xu; Meiqin Yang; Tiefeng Huang; Yifan Kou; et al. (Journal for ImmunoTherapy of Cancer)
CKLF (chemokine-like factor)-like MARVEL transmembrane domain-containing family member 4 (CMTM4), belonging to the CMTM family of transmembrane domain proteins, plays a significant role in the initiation, progression, and metastasis of cancer. Nevertheless, its involvement in tumor immunity remains elusive. In the present investigation, we observed an upregulation of CMTM4 expression in patients with cervical cancer (CC), which also serves as a prognostic indicator for patients with CC. In vitro experiments and therapeutic models have demonstrated that CMTM4 upregulates the expansion of myeloid-derived suppressor cells (MDSCs) in the tumor microenvironment via the CCL2 (C–C motif chemokine ligand 2)/CCR2 (C–C motif chemokine ligand 2) and IL-6 (interleukin-6)/GP130 (glycoprotein 130) axes. This process exerts immunosuppressive effects and promotes the occurrence and progression of CC. Mechanistically, CMTM4 interacts and stabilizes PHB2 (prohibitin 2) through post-translational modification, which further induces activation of the STING (stimulator of interferon genes)/TBK1 (TANK-binding kinase 1)/STAT6 (signal transducer and activator of transcription 6) pathway, facilitating the nuclear translocation of STAT6 which binds to the CCL2/IL-6 promoter, leading to the upregulation of CCL2/IL-6 transcription expression. Importantly, targeting CMTM4 with CMTM4-small interfering RNA enhanced the effectiveness of anti-programmed cell death protein 1 (anti-PD-1) therapy. Our study identifies CMTM4 as a crucial determinant guiding the homing of MDSCs to CC, thereby contributing to MDSCs-mediated immune suppression and tumor progression. The combination of CMTM4 inhibition and anti-PD-1 treatment shows promising antitumor efficacy against CC. These findings offer novel insights into the tumor microenvironment and have the potential to inform the development of innovative immunotherapy approaches for CC.